Promotion Mix Analysis Of Customer Interest In Gold Savings Products: Study at PT. Pegadaian Syariah Landungsari Branch - Martio, Nazmi Ahmad (International Journal of Management and Business, 2024)
The aim of the research is to determine that customer interest in utilizing Gold Savings products at PT. Pegadaian Syariah Landungsari Branch is influenced by public relations, sales promotions, personal sales, and advertising. This investigation used a descriptive quantitative research design, analyzing data from customer questionnaires for Gold Savings and then summarizing the findings of that analysis. The findings of the study indicate that at the PT. Pegadaian Syariah Landungsari Branch, the promotional mix has a significant impact on consumer decisions and interest in saving. This is evident in the sales promotion variable (Sales Promotion) with an average strongly agree percentage of 62.5% and the advertising variable (Adverising), which has an average strongly agree percentage of 61%. the variable for personal selling (Personal Selling), which has an average of The public relations variable has an average percentage of 60% strongly agree, and the overall percentage is 60% strongly agree. This indicates that the PT. Pegadaian Syariah Landungsari Branch marketing mix has been successful, with an average per variable of over 50%.